Characterization of Aroma Active Compound Production during Kombucha Fermentation: Towards the Control of Sensory Profiles - Sarah Suffys; Gaëtan Richard; Clément Burgeon; Pierre-Yves Werrie; Eric Haubruge; Marie-Laure Fauconnier; Dorothée Goffin (Foods, 2023)
Since the sensorial profile is the cornerstone for the development of kombucha as a beverage with mass market appeal, advanced analytical tools are needed to gain a better understanding of the kinetics of aromatic compounds during the fermentation process to control the sensory profiles of the drink. The kinetics of volatile organic compounds (VOCs) was determined using stir bar sorptive extraction—gas chromatography—mass spectrometry, and odor-active compounds were considered to estimate consumer perception. A total of 87 VOCs were detected in kombucha during the fermentation stages. The synthesis of mainly phenethyl alcohol and isoamyl alcohol probably by Saccharomyces genus led to ester formation. Moreover, the terpene synthesis occurring at the beginning of fermentation (Δ-3-carene, α-phellandrene, γ-terpinene, m- and p-cymene) could be related to yeast activity as well. Principal component analysis identified classes that allowed the major variability explanation, which are carboxylic acids, alcohols, and terpenes. The aromatic analysis accounted for 17 aroma-active compounds. These changes in the evolution of VOCs led to flavor variations: from citrus-floral-sweet notes (geraniol and linalool domination), and fermentation brought intense citrus-herbal-lavender-bergamot notes (α-farnesene). Finally, sweet-floral-bready-honey notes dominated the kombucha flavor (2-phenylethanol). As this study allowed to estimate kombucha sensory profiles, an insight for the development of new drinks by controlling the fermentation process was suggested. Such a methodology should allow a better control and optimization of their sensory profile, which could in turn lead to greater consumer acceptance.